Diary of a wimpy kid hard luck - Kinney, Jeff (Waterville, Maine Thorndike Press, a part of Gale, Cengage Learning, 2017)
"Greg Heffley's on a losing streak. His best friend, Rowley Jefferson, has ditched him, and finding new friends in middle school is proving to be a tough task. To change his fortunes, Greg decides to take a leap of faith and turn his decisions over to chance. Will a roll of the dice turn things around, or is Greg's life destined to be just another hard-luck story?"--
Originally published in a slightly different form by Amulet Books in 2013
1 15
Keywords: Large type books; Diaries -- Fiction; Friendship -- Fiction; Humorous stories; Large type books; Luck -- Fiction; Middle schools -- Fiction; Schools -- Fiction